Die Entwicklung der Viehwirtschaft in Neuseeland - Sellenberg, Erika (ERDKUNDE, 1960)
The favourable natural conditions in New Zealand are an important basis for her prosperous livestock industry. To the first inhabitants, the Maoris, domesticated animals were unknown; pigs, sheep, and cattle, as well as other animals from Europe, were brought into the country by European settlers. After the subsistence agriculture of the early decades of colonization, the age of pastoral farming began about the middle of last century. Very extensive raising of sheep for wool in the tussock-grasslands of the South Island was the first type of farming to produce for export. In the following years, large areas in the North Island were cleared of their native bush and scrub in order to be used as extensive hill-country pastures for sheep; and in the plains of the South Island arable farming was introduced. But it was not before the last decades of the century that impetus was given to intensive livestock farming on the marginal plains. Fat stock production and dairying were now furthered by improved farming methods, new farm machinery and by the invention of refrigeration, which has made possible the shipment of perishable products to distant markets. Since then, intensification and rationalization of all types of farming have been important elements in New Zealand’s livestock industry and, through the changes in her economic history, have resulted in making those remote islands in the Pacific one of the world’s foremost suppliers of livestock products.